Sensory Feedback in Hand Prostheses: A Prospective Study of Everyday Use - Wijk, Ulrika; Carlsson, Ingela K.; Antfolk, Christian; Björkman, Anders; Rosén, Birgitta (Frontiers in Neuroscience, 2020)
Sensory feedback in hand prostheses is lacking but wished for. Many amputees experience a phantom hand map on their residual forearm. When phantom hand map is touched, it is experienced as touch on the amputated hand. A non-invasive sensory feedback system, applicable to existing hand prostheses can transfer somatotopical sensory information via PHM. The aim was to evaluate how forearm amputees experienced a non-invasive sensory feedback system used in daily life over a four-week period. Methods: This longitudinal cohort study, included seven forearm amputees. A non-invasive sensory feedback system was used over four weeks. For analysis, a mixed method was used, including quantitative tests and interviews. A directed content analysis with predefined categories: sensory feedback from the prosthesis, agency, body ownership, performance in activity and suggestions for improvements was applied. Results: The results from interviews showed that sensory feedback was experienced as a feeling of touch which contributed to an experience of completeness. However, the results from the questionnaire showed that the sense of agency and performance remained unchanged or deteriorated. The ability to feel and manipulate small objects was difficult and a stronger feedback was wished for. Phantom pain was alleviated in four out of five patients. Conclusion: This is the first time a non-invasive sensory feedback system for hand prostheses was implemented in home environment. The qualitative and quantitative results diverged. The sensory feedback was experienced as a feeling of touch which contributed to a feeling of completeness, linked to body ownership. The qualitative result was not verified in the quantitative measurements.